[Evelyn F. Streng At Lava Pillar on Snæfellsnes Peninsula] (1975)
Photograph of Evelyn F. Streng at a lava rock pillar on Snæfellsnes Peninsula. The grey, jagged rock sits on a grassy cliff in an L-shaped formation. A similar pillar formation sits to the right of the main formation. A black platform sits along the light blue water to the left. Streng stands to the right wearing a white beanie hat, a brown jacket, and blue jeans.